Correlation of anthropometric characteristics and movement behavior with lower extremity muscle power and dynamic knee valgus in adolescent basketball athletes - Stojiljkovic, Aleksandar; Karagianni, Eleni; Varsamo, Antoniou; Batalik, Ladislav; Pepera, Garyfallia (The Journal of sports medicine and physical fitness, 2024)
BACKGROUND: The anthropometric characteristics of adolescent basketball athletes can determine their ability to produce muscle power. Lack of physical activity (PA) level or an increased sedentary life seem to be associated with the overall health status and the occurrence of knee injuries. The aim of this paper was to identify possible correlations between anthropometric characteristics, body composition, exposure time to electronic devices or screen time (ST), and PA level along with muscle power and dynamic knee valgus (DKV) in young basketball athletes. METHODS: Anthropometric and demographic characteristics were recorded. PA level was assessed through the International Physical Activity Questionnaire, and ST was assessed through a single question from the HELENA study. The Counter Movement Jump test was used for the evaluation of the lower limb muscle power, while the Single Leg Drop Jump test was used for the evaluation of the DKV via two-dimensional (2D) kinematic analysis. RESULTS: One hundred twenty-five adolescent basketball athletes (66.4% boys), 12 to 17 years old (13.94±1.58 years) participated. The Pearson index showed a statistically significant positive correlation between muscle power and height (r=0.788, P<0.001), while the Spearman Index showed a more minor but equally statistically significant positive correlation with Body Mass Index (rs=0.651, P<0.001) and age (rs=0.579, P<0.001). The ST (rs= -0.194, P=0.03) showed a weak negative correlation with DKV, while PA (r=0.85, P<0.001) showed a high, statistically significant, positive correlation. CONCLUSIONS: A high level of PA could play a key role in compensating and thus reducing the negative effects of high exposure to ST on the DKV.
Keywords: Body Height; Movement; Female; Anthropometry; dítě; pohyb; ženské pohlaví; Knee Joint; svalová síla; Adolescent; basketbal; lidé; antropometrie; tělesná výška; Muscle Strength; biomechanika; Basketball; Male; složení těla; index tělesné hmotnosti; Body Composition; Child; Lower Extremity; mužské pohlaví; kolenní kloub; Body Mass Index; dolní končetina; mladiství; Biomechanical Phenomena; Humans